ANALISIS FAKTOR YANG MEMPENGARUHI RETENSI KARYAWAN - Adzka, Safaat Aufahasan Adzka; Perdhana, Mirwan Surya (Diponegoro Journal of Management, 2017)
Competitive resource management is an important element of the company. The management of human resources will impact on the company's strategic plan. The success of corporate investment in human resources is determined by the success of employee retention strategies implemented.This study aims to determine what factors affect the retention of employees. After the observation of 15 previous studies on employee retention, 14 factors have been found to affect employee retention in various cultural contexts. These 14 factors are then selected through brainstorming of 8 employee retention experts consisting of 5 practitioners and 3 academics.The result of this research is that there are 6 factors that have the most influence on employee retention that is reward, compensation, leadership, career development, training and development, and job satisfaction. Then the best ranking achieved by reward.